Russian Non-Interventional Study of the Efficacy and Tolerability of Rifaximin-α Therapy in Patients with Uncomplicated Diverticular Disease under the Conditions of Outpatient Practice - O. S. Shifrin; E. A. Poluektova; A. V. Korolev; T. I. Semenova; M. V. Shein; G. N. Leksikova; O. A. Tokareva; O. E. Davydova; P. S. Andreev; S. E. Katorkin; A. A. Chernov; A. V. Zhuravlev; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2020)
Aim. This observational (non-interventional) study was aimed at obtaining data on practitioners’ commitment to prescribing rifaximin-α therapy to patients with uncomplicated diverticular disease (UDD), to assess patients’ adherence to such prescriptions, as well as to assess physicians’ and patients’ satisfaction with this drug under the conditions of outpatient practice.Materials and methods. 27 research physicians in 22 research centres located in 15 Russian cities and 250 patients participated in an open, prospective multicentre observational study. The observation lasted for 6 months with an interim assessment after 3 months. Physicians’ prescription of rifaximin-α (dose, duration of administration, number of prescribed courses) was evaluated, as well as patients’ compliance expressed as the ratio of the actual number of taken pills to the number of prescribed pills during each course according to the MMAS-4 scale. Such symptoms, as abdominal pain, constipation, diarrhea, flatulence and tenesmus were evaluated using a 4-score scale. At the end of the study, physicians’ and patients’ satisfaction with the treatment was evaluated using a 5-score scale.Results. One fifth — 52 patients (20.8%)—had received rifaximin-α therapy prior to inclusion in the study. Most frequently, rifaximin-α therapy was prescribed monthly at a dose of 400 mg 2 times a day for 7 days. 67.6% of patients received 6 courses of treatment during the study period. The proportion of patients who received more than one course of treatment over 6 months was 97.6%. During almost all treatment courses (97.5%), patients’ compliance was more than 80%. The total score of symptom intensity decreased from 5.6 at the inclusion visit, to 2.2 points at the second visit and to 0.9 points at the end of the observation. A statistically significant (p <0.05) positive dynamics was observed in relation to all evaluated symptoms (abdominal pain, constipation, diarrhea, flatulence, tenesmus). By the end of the study, 59.6% of patients and 68.8% of physicians rated the treatment results as “excellent”, 25.2% of patients and 20.4% of doctors as “good”.Conclusions. During the observation, a significant decrease in the severity of UDD symptoms, such as abdominal pain, constipation, diarrhea, flatulence and tenesmus was noted. No adverse effects associated with rifaximin-α were reported. The data obtained confirm the previously published results of randomized controlled trials on the efficacy and safety of rifaximin-α in UDD.